Socio-Economic Study on the Feasibility of Kisar Sheep Farming on Kisar Island, Southwest Maluku Regency, Maluku Province - Pieter Melianus Ririmase; Paul Melkianus Puttileihalat; Christian W. Patty (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to describe breeders who carry out kissar sheep farming activities, as well as analyze the income and profits of farmers. This research was conducted on Kisar Island, Southwest Maluku Regency using a survey method and a purposive sampling of 25 farmers. Data analysis was carried out quantitatively. 52 percent of breeders are aged 31-50 years, 76 percent have an elementary school education, 36 percent of breeders have a business duration of > 21 years, 20 percent have a main job as farmers, and only 4 percent of breeders. The sheep farming business on Kisar Island suffers losses and does not increase income because the labor sacrificed is quite large, and every year there is a decline in the sheep population due to limited capital to expand its business so that it is filled with others because of the family's economic pressure, marketing is still carried out.